2009
DOI: 10.1179/174327809x419177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shot peening on high temperature oxidation behaviour of boiler steel: experimental results and simulation

Abstract: A prediction of the service life of boiler steels in aggressive atmospheres requires a full understanding of the degradation mechanisms of the material due to high temperature oxidation. The developed model is a useful tool to simulate such degradation processes under complex conditions and hence, to contribute to new mechanism based life prediction methods. In the present study the effect of shot peening on the oxidation behaviour is studied and given importance to model the behaviour and simulate the effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[27][28][29][30][31][32] The isotopic tracer experiments indicated that shot-peening and applied stresses have very little influence on the inward oxygen diffusion, thus eliminating enhancement due to a greater contribution from inward anionic growth. This suggests that the shot-peening and mechanical loads applied to polished samples act to influence the diffusivity of the oxidized solute species (i.e., chromium and titanium) in the parent and recrystallized alloy, [33][34][35] and this is proposed to result from defects induced from creep deformation. This could explain the increased internal oxidation kinetics realized in the polished specimens under load.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30][31][32] The isotopic tracer experiments indicated that shot-peening and applied stresses have very little influence on the inward oxygen diffusion, thus eliminating enhancement due to a greater contribution from inward anionic growth. This suggests that the shot-peening and mechanical loads applied to polished samples act to influence the diffusivity of the oxidized solute species (i.e., chromium and titanium) in the parent and recrystallized alloy, [33][34][35] and this is proposed to result from defects induced from creep deformation. This could explain the increased internal oxidation kinetics realized in the polished specimens under load.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a more effective alloy diffusion coefficient is obviously of benefit in rapidly achieving and maintaining a steady growth of protective chromia. In recent studies, shotpeening martensitic steels show an improvement in the oxidation behaviour, but this is not yet sufficient to replace austenitic steels [7,8]. The present study reports an improvement of passification of these steels by 50%.…”
Section: Introductionmentioning
confidence: 47%
“…2a shows a small dislocation density near the metal sub surface (area next to the surface). It is known that the shot-peening influences the microstructure by introducing dislocations in the effected area [7]. TEM studies showed the high dislocation density at the sub surface of SPCr-18 as in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…It has been shown by several authors that cold work and surface finish (e.g. shot blasting) can strongly influence the oxidation behaviour and promotes the formation of protective layers on the surface of the material [4][5][6][7]. The reason can be attributed to the fact that the cold work influences the microstructure near to the surface, i.e., dislocations and grain boundaries are introduced, which can act as easy diffusion paths for Cr supporting the formation of Cr-oxide at the surface.…”
Section: Introductionmentioning
confidence: 99%